2019
DOI: 10.1038/s41419-019-1410-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia preconditioning promotes bone marrow mesenchymal stem cells survival by inducing HIF-1α in injured neuronal cells derived exosomes culture system

Abstract: Bone marrow derived stem cells (BMSCs) transplantation are viewed as a promising therapeutic candidate for spinal cord injury (SCI). However, the inflammatory microenvironment in the spinal cord following SCI limits the survival and efficacy of transplanted BMSCs. In this study, we investigate whether injured neuronal cells derived exosomes would influence the survival of transplanted BMSCs after SCI. In order to mimic the microenvironment in SCI that the neuronal cells or transplanted BMSCs suffer in vivo, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 47 publications
4
72
0
Order By: Relevance
“…However, none of the 3 miRNAs could serve as a biomarker for predicting storage lesions and monitoring the quality of RBC units. Although mature RBCs can not generate new RNA molecules and exosomal RNA molecules are possibly degraded with the extending storage time, we can find increasing of these 3 miRNAs during storage and attribute this phenomenon to the changes in microenvironment of stored RBCs which were previously reported [32], leading to the changes in contents of exosomes [13,27,29,30]. However, high abundance of exosomal miR-451a may mark it as an important regulatory miRNA in the recipients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, none of the 3 miRNAs could serve as a biomarker for predicting storage lesions and monitoring the quality of RBC units. Although mature RBCs can not generate new RNA molecules and exosomal RNA molecules are possibly degraded with the extending storage time, we can find increasing of these 3 miRNAs during storage and attribute this phenomenon to the changes in microenvironment of stored RBCs which were previously reported [32], leading to the changes in contents of exosomes [13,27,29,30]. However, high abundance of exosomal miR-451a may mark it as an important regulatory miRNA in the recipients.…”
Section: Discussionmentioning
confidence: 78%
“…However, the role and mechanisms of exosomes (RBCs-derived) in transfusion-related immunomodulation await clear elucidation. Secretion and contents of exosomes are regulated by different microenvironments [13,27,29,30]. The contents of exosomes (RBC-derived), stored in ACD-A solution, are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic preconditioning (HPC) could advance the efficiency of stem cell therapy. Indeed, in multiple studies, the exposure of stem cells to hypoxic conditions prior to transplantation resulted in improved survival, enhanced proliferation and differentiation, and reduced senescence [ 41 , 42 , 43 , 44 ]. The alternation of hypoxic and normal oxygen conditions promotes multipotency and the expression of pro-survival genes and trophic factors in MSCs [ 31 , 45 ].…”
Section: Stem Cell Preconditioning For MI Treatmentmentioning
confidence: 99%
“…Shao et al (2017) found that mesenchymal stem cell-derived exosomes (MSC-Exos) alleviated the inflammatory response and improved cardiac function by decreasing the infiltration of inflammatory cells in the infarct area via down-regulating the expression of CD68. In order to enhance their cardiaoprotective effect, exosomes can be pretreated by hypoxia preconditioning (Luo et al, 2019), gene programming (Wang et al, 2018), or drug intervention (Huang et al, 2019). Pan et al (2019a) showed that exosomes derived from miR-146a-modified adipose-derived stem cells ADSC-Exos inhibit the release of interleukin-6 (IL-6), interleukin-1β (IL-1β ) and tumor necrosis factor-α (TNF-α), as well as reducing the local inflammatory response, improving the local microenvironment, and attenuating acute myocardial infarction-induced myocardial damage via the down-regulation of early growth response factor 1 (EGR1).…”
Section: Myocardial Infarctionmentioning
confidence: 99%